Integrated techno-economic and environmental analysis of guayule rubber production. (10th November 2020) - Sproul, Evan; Summers, Hailey M.; Seavert, Clark; Robbs, Joram; Khanal, Sita; Mealing, VeeAnder; Landis, Amy E.; Fan, Neng; Sun, Ou; Quinn, Jason C.
Abstract: Persistent drought poses a significant risk to farmers in the southwest United States. Adopting drought tolerant crops that yield high value products will help mitigate this risk. One potential crop is guayule, which is known for its high natural rubber content. In this work, a process model was created to quantify all materials and energy required to cultivate, harvest, transport, and extract guayule rubber and co-products. This process model was used to enable the first concurrent techno-economic and environmental analysis of guayule. The techno-economic and environmental results include two scenarios: 1) a baseline scenario in which bagasse and resin are sold at predefined values and 2) an on-site heat and power scenario in which bagasse is combusted to generate heat and electricity. The result of the techno-economic analysis for the baseline scenario was a minimum rubber selling price of 3.08 per kg, with co-products of resin and bagasse being sold at 1.00 and 0.10 per kg, respectively. Baseline environmental results show that the largest impacts come from the use of fertilizers in agriculture and natural gas in the rubber extraction facility. The on-site heat and power analysis found an increased minimum rubber selling price of 4.07 per kg, but also a 61% decrease in global warming emissions. Discussion focuses on leveraging results to further the development of guayule by identifying high impact areas where future research may simultaneously reduce costs and environmental impacts. Graphical abstract: Image 1 Highlights: Evaluation of guayule rubber: agriculture, transportation, and extraction. Baseline minimum guayule rubber selling price determined to be 3.08 per kg. Harvest yield, rubber percentage, and coproduct values have impact on rubber price. On-site heat and power from bagasse reduces greenhouse gases but increases costs.